Predictors and Outcomes of Transfers from Peritoneal Dialysis to Hemodialysis. Issue 3 (May 2015) - Lan, Patrick G.; Clayton, Philip A.; Saunders, John; Polkinghorne, Kevan R.; Snelling, Paul L.
Introduction: Peritoneal dialysis (PD) patients are commonly required to transfer to hemodialysis (HD), however the literature describing the outcomes of such transfers is limited. The aim of our study was to describe the predictors of these transfers and their outcomes according to vascular access at the time of transfer. Methods: A retrospective cohort study using registry data of all adult patients commencing PD as their initial renal replacement therapy in Australia or New Zealand between 2004 – 2010 was performed. Follow-up was until 31 December 2010. Logistic regression models were constructed to determine possible predictors of transfer within both 6 and 12 months of PD commencement. Cox analysis and competing risks regression were used to determine the predictors of survival and transplantation post-transfer. Results: The analysis included 4, 781 incident PD patients, of whom 1, 699 transferred to HD during the study period. Logistic models did not identify any clinically useful predictors of transfer within 6 or 12 months (c-statistics 0.54 and 0.55 respectively). 67% of patients commenced HD with a central venous catheter (CVC). CVC use at transfer was associated with increased mortality (hazard ratio 1.37, 95% confidence interval (CI) 1.11 – 1.68, p = 0.003) and a borderline significant reduction in the incidence of transplantation (subhazard ratio 0.76, 95% CI 0.58 – 1.00, p = 0.05). Conclusions: It is difficult to predict the transfer to HD for incident PD patients. PD patients who commence HD with a CVC have a higher risk of mortality and a lower likelihood of undergoing renal transplantation.